The Impact of Quality of Banking Services on the Customer Satisfaction in Small and Medium Banks - Alall, Hussein Adnan Essa (South Asian Journal of Social Sciences and Humanities, 2024)
The study aims to test the nature of the association between the quality of banking services and its role in achieving customer satisfaction. This study tested the quality of banking services in south Asian countries and identified the various relative importance’s representing the quality of banking services. The study included a purposive sample of commercial banks from 139 individual banks, and the study used statistical software STATA to analyse the results. The results presented that there is a positive and important association among the quality of banking services and customer satisfaction. As a result of these challenges, it has become necessary for banking organizations to take into account the philosophy of customer satisfaction, which provides them with a competitive advantage that contributes to achieving high level of profitability.